Lightweight and quantum-resistant authentication for the Internet of Drones (IoD) using Dilithium signatures. - Tawfeeq, Nawar Hayder; Yousif, Mohammed; Al-Shareeda, Mahmood A; Almaiah, Mohammed Amin; Shehab, Rami (International Journal of Innovative Research and Scientific Studies, 2025)
The use of drones in military operations is a growing phenomenon that presents substantial security implications, especially related to authentication, data integrity, and the treatment of cyber threats. While traditional schemes like Elliptic Curve Cryptography (ECC) have computational efficiency, they are susceptible to quantum attacks. To solve the aforementioned problem, in this paper, we design a Lightweight and Quantum Resistant Authentication Protocol for Military IoD Using Dilithium Signatures, which is a post-quantum cryptographic (PQC) method implemented using the PQC solution based on lattice-based cryptographic evidence. The proposed protocol provides quantum-safe mutual authentication of drones, soldiers, and the command center (CC) while also protecting against impersonation attacks and side-channel attacks. In contrast to ECC-based authentication and its vulnerability to Shor’s Algorithm, the proposed system is long-term quantum secure. While Dilithium incurs increased computational and communication costs, our performance evaluations show that it provides security against quantum adversaries and replay attacks, thereby deeming it a worthwhile choice, especially in light of the swift advancements in ASIC technology. In an effort to be truly efficient, signature compression, parallel authentication verification, and an improved key management approach further enhance the scalability of the proposed scheme in the military Internet of Drones (IoD) network. The results substantiate the necessity of deploying full post-quantum authentication schemes to protect UAV networks. We intend to focus on developing energy-saving hardware and optimizations for real-world deployment in future work.